Innovating through digital revolution: The role of soft skills and Big Data in increasing firm performance. Issue 8 (12th September 2019) - Caputo, Francesco; Cillo, Valentina; Candelo, Elena; Liu, Yipeng
Abstract : Purpose: The purpose of this paper is to investigate the relations among soft skill, information technologies and Big Data for building a possible bridge able to link human and technology dimensions for increasing firm performance. Design/methodology/approach: Using the Business-focused Inventory of Personality, work personality of 4, 758 human resources engaged in 72 high-tech European firms has been analyzed and its relations with firms' investment in Big Data and firms' economic performance have been tested using the structural equation modeling (SEM). Findings: The research shows the existence of strong relations between some elements of human resources' personality such as the work motivation and the social competencies and the firms' economic performance. At the same time, the research clarifies the mediated effect of firms' investment in Big Data in the relations between human resources' organizational behavior and the firms' economic performance. Originality/value: The paper extends previous managerial contributions about Big Data management and human resource management providing evidence on which build more effective managerial models in the era of digital transformation.